Abundance, composition and distribution of epiphytes on Enhalus acoroides in Taklong Island National Marine Reserve (TINMR), Nueva Valencia, Guimaras. - Roperos, Jandeil B.
Seagrass community plays a crucial role in the functioning of shallow estuaries and coastal environment as it provides primary and secondary productions for higher-level marine organisms. Seagrass blades function as attachment to many floral and faunal epiphytes. This study characterizes the abundance, composition and distribution of epiphytes on Enhalus acoroides collected in tow sites in Taklong Island National Marine Reserve (TINMR), Guimaras namely ? Banago and Calaparan. Results showed significant difference (F=0.078) P=0.01) in the mean epiphytic densities between Banago (17,781 ind/m2) and Calaparan (6,324 ind/m2) likely due to site differences in wave exposure.